Prevalence and Characteristics of Enteric Pathogens Detected in Diarrhoeic and Non-Diarrhoeic Foals in Trinidad. (21st June 2012) - Harris, Robin; Sankar, Kerri; Small, Julie-Anne; Suepaul, Rod; Stewart-Johnson, Alva; Adesiyun, Abiodun
Abstract : The study determined the relative importance of Escherichia coli, E. coli O157, Salmonella spp., Clostridium spp., rotavirus, Cryptosporidium spp., and Strongyloides westeri in foal (diarrhoeic and non-diarrhoeic) available for sampling during the foaling season of 2010 and determined their sensitivity to antimicrobial agents. A cross-sectional study was conducted on 164 foals (9 diarrhoeic and 155 non-diarrhoeic) from 15 farms in Trinidad. Isolation and detection of enteric pathogens followed standard methods, and the antibiograms of E. coli and Salmonella spp. were determined using the disc diffusion method. All organisms investigated were detected except E. coli O157. A high prevalence of E. coli (85.0%), Cryptosporidium spp. (64.8%), Strongyloides westeri (35.7%) was seen, but the prevalence was comparatively low for Clostridium spp. (12.9%), Salmonella spp. (4.4%) and rotavirus (2.1%). Only Salmonella spp. was isolated at a statistically significantly (P < 0.05 ;χ 2 ) higher frequency from diarrhoeic (25.0%) than non-diarrhoeic (4.0%) foals. Amongst E. coli isolates, the frequency of resistance was higher in isolates from diarrhoeic compared with non-diarrhoeic foals but the difference was only statistically significant (P < 0.05 ;χ 2 ) for tetracycline. All isolates of Salmonella spp. were sensitive to streptomycin and sulphamethoxazole/trimethoprim, a finding that may have therapeutic significance.